Konsep Whistleblower dan Justice Collaborator Dalam Tindak Pidana Korupsi - Fathony Karuniawan (Fakultas Hukum Universitas Mataram, 2017)
The purpose of this research is to know and analyze the basis of judicial consideration by the judge in deciding case of Number 21 / PUU-XII / 2014. Secondly to know and analyze the implication of decision of Constitutional Court of Republic of Indonesia Number 21 / PUU-XII / 2014. Scope of research focused on the formulation of the problem in this research. In this study using normative research The result of research is the consideration of the Constitutional Court in deciding cases Number 21 / PUU-XII / 2014 especkiially against Article 77 KUHAP in order to provide protection of human rights for suspects. The implications of the verdict are of theoretical implications and practical implications